Innovation In Patchwork Waste Processing Using Fabric Manipulating Techniques And Design Thinking Approach - Madani Aisyiyah, Wulan; Widiatmoko Soewardikoen, Didit; Azhar, Hanif; Nurhadiansyah, Mahendra (Advances In Social Humanities Research, 2024)
Fashion waste is a global concern due to its large production volume. Therefore, waste management is a major concern in the industry to reduce negative impacts on the environment. The case study in this study is on a garment factory on Jalan Tamim. The waste produced by this garment needs to be considered in environmental management on Jalan Tamim Bandung. It highlights the urgency of implementing more sustainable production practice innovations by utilizing fabric scraps. The design approach method is used to provide a deep understanding of the problem's urgency that can produce design solutions with the Design Thinking stages, namely, emphasizing, defining, ideating, prototyping, and testing. The design results are expected to be an alternative strategy for utilizing fabric scraps in the context of sustainable fashion using fabric manipulation techniques